Asymptomatic Left Ventricle Systolic Dysfunction - Jaskanwal D Sara; Takumi Toya; Riad Taher; Amir Lerman; Bernard Gersh; Nandan S Anavekar (European Cardiology Review)
Heart failure is a common debilitating illness, associated with significant morbidity and mortality, rehospitalisation and societal costs. Current guidelines and position statements emphasise the management of patients with overt symptomatic disease, but the increasing prevalence of congestive heart failure underscores the need to identify and manage patients with early left ventricular dysfunction prior to symptom onset. Asymptomatic left ventricular systolic dysfunction (ALVSD), classified as stage B heart failure, is defined as depressed left ventricular systolic function in the absence of clinical heart failure. Early initiation of therapies in patients with presumed ALVSD has been shown to lead to better outcomes. In this article, the authors clarify issues surrounding the definition and natural history of ALVSD, outline clinical tools that may be of value in identifying patients with ALVSD and highlight potential opportunities for future investigations to better address aspects of our understanding of this complex syndrome.